CAN UNIVERSITIES MEET THEIR MANDATE TO BE SOCIALLY CRITICAL AS WELL AS CONSTRUCTIVE - van der Walt, J.L.; F.J. Potgieter, F.J. Potgieter; Wolhuter, C.C. (South African Journal of Higher Education, 2016)
This article defends the claim that two conditions facilitate sustainable development, namely a democratic citizenry and social justice, and that in establishing these, the university is indispensible and ideally placed. With the use of an experiential, interpretive approach the social critique function of the university is examined, as well as the role of the university in reinforcing a culture of democratic citizenry and thereby of promoting social justice. The last part of the article delineates the current global higher education revolution, and identifies the opportunities and threats posed by that revolution regarding the university’s discharge of these two functions. The article concludes with a warning to scholars to be aware of both the opportunities for consolidating their scholarship and the concomitant threats to their academic autonomy. Key words: higher education, university, social responsibility, social justice, democratic citizenry, global higher education revolution